RELATIVE WEIGHT OF SMALL INTESTINE AND LYMPHOID ORGAN OF FINISHER PERIOD BROILER CHICKEN AT DIFFERENT REARING TEMPERATURES - Rotiah Rotiah; Endang Widiastuti; Dwi Sunarti (Study Program of Animal Science, 2019)
As a tropical country, Indonesia has a diverse air temperature range, reaching more than 34 °C during the day. This temperature is not suitable for rearing of broiler chickens because it induces heat stress. Heat stress can reduce the broilers immune system, it can also cause various diseases, the decrease in growth rate and production and making it uneconomical. Heat stress can inhibit the absorption of nutrients in the digestive tract which can affect the weight of the digestive organs and affect the relative weights of lymphoid organs of broiler chicken. The research was conducted at Poultry Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang on 08-23 March 2018. This study aims to examine the relative weights of the small intestine and the relative weight of lymphoid organs of finisher period broiler chicken which are reared in different temperatures. The material used in this research is broiler chicken strain CP 707 male finisher period (age 21 days) as many as 20 chicken with an average body weight of 1167 g. The research used the t-test with 2 treatments of 10 replications. The treatment applied is T1: heat temperature and T2: comfortable temperature. The parameters observed were relative weights of the small intestine (duodenum, jejenum, ileum) and lymphoid organs (bursa fabricius, thymus, spleen). The results of the study showed that the relative weight of the small intestine consisting of the duodenum, jejunum and ileum at heat and comfortable rearing temperatures was respectively 0.25%; 0.66%; 0.55% and 0.34%; 0.79%; 0.71%, as well as the relative weight of lymphoid organs consisting of bursa fabricius, thymus and spleen exchanges at heat and comfortable rearing temperatures of 0.07%; 0.23%; 0.11% and 0.09%; 0.28%; 0.16%. The rearing temperature is significantly different with the relative weight of the small intestine and lymphoid organs of finisher period broiler (P<0.05). The conclusion of the research was that finisher period broiler chicken reared at a comfortable temperature have a higher relative weight of small intestine and lymphoid organs compared to broiler finisher period which are maintained at hot temperatures.